Genome-wide identification and expression analysis of the Auxin-Response factor (ARF) gene family in Medicago sativa under abiotic stress - Fenqi Chen; Jinqing Zhang; Xue Ha; Huiling Ma (BMC Genomics, 2023)
Abstract Background Alfalfa (Medicago sativa) is the most widely planted legume forage and one of the most economically valuable crops in the world. The periodic changes in its growth and development and abiotic stress determine its yield and economic benefits. Auxin controls many aspects of alfalfa growth by regulating gene expression, including organ differentiation and stress response. Auxin response factors (ARF) are transcription factors that play an essential role in auxin signal transduction and regulate the expression of auxin-responsive genes. However, the function of ARF transcription factors is unclear in autotetraploid-cultivated alfalfa. Result A total of 81 ARF were identified in the alfalfa genome in this study. Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were analyzed, identifying that ARF genes are mainly involved in transcriptional regulation and plant hormone signal transduction pathways. Phylogenetic analysis showed that MsARF was divided into four clades: I, II, III, and IV, each containing 52, 13, 7, and 9 genes, respectively. The promoter region of the MsARF gene contained stress-related elements, such as ABRE, TC-rich repeats, MBS, LTR. Proteins encoded by 50 ARF genes were localized in the nucleus without guide peptides, signal peptides, or transmembrane structures, indicating that most MsARF genes are not secreted or transported but only function in the nucleus. Protein structure analysis revealed that the secondary and tertiary structures of the 81 MsARF genes varied. Chromosomal localization analysis showed 81 MsARF genes were unevenly distributed on 25 chromosomes, with the highest distribution on chromosome 5. Furthermore, 14 segmental duplications and two sets of tandem repeats were identified. Expression analysis indicated that the MsARF was differentially expressed in different tissues and under various abiotic stressors. The quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis showed that the expression profiles of 23 MsARF genes were specific to abiotic stresses such as drought, salt, high temperature, and low temperature, as well as tissue-specific and closely related to the duration of stress. Conclusion This study identified MsARF in the cultivated alfalfa genome based on the autotetraploid level, which GO, KEGG analysis, phylogenetic analysis, sequence characteristics, and expression pattern analysis further confirmed. Together, these findings provide clues for further investigation of MsARF functional verification and molecular breeding of alfalfa. This study provides a novel approach to systematically identify and characterize ARF transcription factors in autotetraploid cultivated alfalfa, revealing 23 MsARF genes significantly involved in response to various stresses.